Relações afetivas em litígio e a mediação familiar - Antonio, Maria de Lourdes Bohrer (2013)
This study aims at analyzing the affective family relationships between the parents of children/adolescent children in litigation phase and at learning the meaning of family mediation. Our main theoretical framework lies on the philosopher Spinoza and on the contemporaries Morin and Maturana. We conducted a quantitative study through which we located the insertion of Custody Petition and Regulatory Visits as the main demand of the Mediation Sector of Family and Probate Courts in the District of Santos, and we profiled the protagonists of those petitions, i.e., the claimants and the defendants, parents of the children/adolescent children. The research was limited to a three-year window (2008-2010). With the profile resulting from the quantitative study, we conducted a qualitative study. We have carried out semi-structured interviews with seven families as well as with five judges who referred users to our Mediation Sector. The qualitative research was analyzed using two axes: family affective relationships and family mediation. We understand that family relationships of parents in litigation is marked by the desire to love living with their children and by the realization of rights. Although this action is primarily a suffering for having been driven by a sad passion, litigation is a measure to cope with an ethical-political suffering. This action seeks harmony, even though it may seem otherwise. The judicial family mediation is a judiciary proposal which contributes to harmony be a path to meeting with a state of peace. Peace is power of life, happiness and freedom that are expressed in the material and spiritual conditions of human existence in society. The judicial family mediation is a work process performed by a qualified professional (or team) with his/her own interdisciplinary methodology, having an affective and ethical basis, so that two or more people who have family ties - whether by blood or not - and who are going through a litigation phase look for more responsible, autonomous and enforceable answers on the conflict. The qualified professional does that under the perspective of a culture of peace and human rights. We conclude that family relationships in litigation are configured in a contemporary expression of the social issue and that mediation is revealed as one of the most important tools for dealing with it as part of a policy. The social worker is a relevant subject in planning and implementing that policy